Density and domination: Catholic materiality and the workings of history in Paris. (14th April 2022) - OLIPHANT, ELAYNE
ABSTRACT: The question whether Europe's Christian churches and monasteries are "religious" or "secular" distracts us from something far more significant: Europe's historical participation in systems of enslavement and expropriation. While these solid buildings seem to demand that we pay attention to them in their "density, " such a focus overlooks their role in reaffirming the boundaries and morality of the dominant group, which, in France, is formed through a convergence of Whiteness and Catholicism. Following a model laid out by Michel‐Rolph Trouillot, I analyze how Paris's Roman Catholic churches participate in the workings of history as sources, archives, narratives, and history. At each stage in their production, these churches have helped silence violent aspects of French history, including slavery and colonialism, while affirming the superiority of White Christian man. [ heritage, density, workings of history, silences, Catholicism, Catholic materiality, Paris, France, Europe ]